Dorsal stress fibers, transverse actin arcs, and perinuclear actin fibers form an interconnected network that induces nuclear movement in polarizing fibroblasts - Maninová, Miloslava; Vomastek, Tomáš (The FEBS journal, 2016)
In polarized motile cells, stress fibers display specific three-dimensional organization. Ventral stress fibers, attached to focal adhesions at both ends, are restricted to the basal side of the cell and nonprotruding cell sides. Dorsal fibers, transverse actin arcs, and perinuclear actin fibers emanate from protruding cell front toward the nucleus and toward apical side of the cell. Perinuclear cap fibers further extend above the nucleus, associate with nuclear envelope through LINC (linker of nucleoskeleton and cytoskeleton) complex and terminate in focal adhesions at cell rear. How are perinuclear actin fibers formed is poorly understood. We show that the formation of perinuclear actin fibers requires dorsal stress fibers that polymerize from focal adhesions at leading edge, and transverse actin arcs that are interconnected with dorsal fibers in spots rich in α-actinin-1. During cell polarization, the interconnected dorsal fibers and transverse arcs move from leading edge toward dorsal side of the cell. As they move, transverse arcs associate with one end of stress fibers present at nonprotruding cell sides, move them above the nucleus thus forming perinuclear actin fibers. Furthermore, the formation of perinuclear actin fibers induces temporal rotational movement of the nucleus resulting in nuclear reorientation to the direction of migration. These results suggest that the network of dorsal fibers, transverse arcs, and perinuclear fibers transfers mechanical signal between the focal adhesions and nuclear envelope that regulates the nuclear reorientation in polarizing cells.
Keywords: Actinin; Cell Line; buněčný převod mechanických signálů; fibroblasty; Actins; Cell Nucleus; kontraktilní svazky; Fibroblasts; transverse arcs; polarita buněk; pohyb; buněčné jádro; Stress Fibers; aktiny; nuclear reorientation; fokální adheze; Cell Movement; aktinin; krysa rodu Rattus; Animals; lidé; perinuclear actin fibers; Cell Polarity; Focal Adhesions; α-actinin-1; Humans; zvířata; Mechanotransduction, Cellular; Movement; Rats; pohyb buněk; actin dorsal fibers; buněčné linie; cell polarity